Characterization of Materials 2012
DOI: 10.1002/0471266965.com085.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Energy Electron Diffraction

Abstract: Low‐energy electron diffraction (LEED) is a common and powerful method for determining the geometric structure of solid surfaces. It has the advantage of being fast and inexpensive relative to many other surface techniques. LEED can provide quick information on the surface unit cell size and geometry of single crystal surfaces, and with more effort can be used to determine the complete surface geometry, i.e. composition, bond lengths and angles. Although LEED has been used primarily as a structural technique, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(99 citation statements)
references
References 73 publications
5
94
0
Order By: Relevance
“…Due to the binding of the surface atoms the surface is in most of the cases more rigid, indicating that the incoming atom experience collisions with a surface atom of an higher effective mass. Experiments of Ar atoms scattered from Pt (111) showed that better agreements with binary collision models are obtained when the surface mass increases to M = 2.5 • M Pt (with M Pt mass of a single platinum atom). [35] 2.1.2 Born-Oppenheimer approximation (BOA)…”
Section: Scattering Dynamics At Surfacesmentioning
confidence: 98%
See 4 more Smart Citations
“…Due to the binding of the surface atoms the surface is in most of the cases more rigid, indicating that the incoming atom experience collisions with a surface atom of an higher effective mass. Experiments of Ar atoms scattered from Pt (111) showed that better agreements with binary collision models are obtained when the surface mass increases to M = 2.5 • M Pt (with M Pt mass of a single platinum atom). [35] 2.1.2 Born-Oppenheimer approximation (BOA)…”
Section: Scattering Dynamics At Surfacesmentioning
confidence: 98%
“…The methodology will subsequently extended to insulating surfaces such as Al 2 O 3 as well as ultra thin films of alumina on a platinum substrate. Finally, inspired by the previous studies of free standing graphene on Pt (111) by Hongyang Jiang, [29] the last chapter will deal with hydrogen scattering experiments performed on an atomically thin graphene layer on Ni (111). This chapter will answer the question of how the different nature of a metal surface influences the reactivity of the adsorbed graphene substrate.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations